How Cultural Values transfer into the Basis for Health Services in the Industry Revolution Era: A Critical Perspective - Agus Joko Susanto; Amos Neolaka; Hafid Abbas; Evi Nopiyanti (Shahid Sadoughi University of Medical Sciences, 2020)
Public health servicesneed serious attention in Indonesia. In fact, the number of health workers is sufficient enough and even excessive in certain areas. This situation is caused by lack of observing principles of the local and national cultural values in carrying out the public health services. We reviewed the published literature over the current satisfactory level of people with regard to thehealth services. Furthermore, we compared the results between residents of the suburb and urban areas regarding the national health services. This critical perspective offerred a concept of health services based on the cultural values with the belief that these values can influence the perceptions, attitudes, and behaviour of individuals, including health workers in rendering health services through health consultations. The purpose was to design a situated cultural learning, through which they can learn to respect and apply cultural values in implementing health services. To implement such cultural values, the concept of industrial revolution 4.0 and 5.0 is also needed, where individuals utilize and work together with machine learning technology or artificial intelligence.